دراسة تحليلية لواقع الإحتراق الوظيفي لدى العاملين في المديرية المركزية لبريد الجزائر (ولاية بومرداس). - وفق مقياس ماسلاش للإحتراق الوظيفي المخصص للخدمات الإنسانية – - شهري, مينة (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى التعرف على مدى إنتشار ظاهرة الإحتراق الوظيفي لدى العاملين بالمديرية المركزية لبريد الجزائر في ولاية بومرداس، وقد تكون مجتمع الدراسة من جميع العاملين بالمديرية المركزية لبريد الجزائر في ولاية بومرداس والبالغ عددهم (60) موظف، حيث طبقت الدراسة عليهم كلهم. ولتحقيق أهداف الدراسة إستخدمت الباحثة إستبانة مكونة من محورين رئيسيين؛ المحور الأول حول البيانات الشخصية للمستجيبن، المحور الثاني حول مقياس ماسلاش للإحتراق الوظيفي (المخصص للخدمات الإنسانية)، وتمت معالجة المعلومات التي تم جمعها لإثبات فرضيات الدراسة بإستخدام البرنامج الإحصائي SPSS. وقد كشفت نتائج الدراسة أن هنالك مستوى متوسط من الإحتراق الوظيفي لدى الموظفين بالمديرية المركزية لبريد الجزائر في ولاية بومرداس. كما أثبتت النتائج كذلك وجود إختلاف في تقييم أبعاد الإحتراق الوظيفي. حيث جاء بعد "الإجهاد" بالمرتبة الأولى بتقييم متوسط، ليأتي بعده بعد "تبلد المشاعر "في المرتبة الثانية بتقييم متوسط كذلك، ليأتي في المرتبة الثالثة والأخيرة بعد "تراجع الشعور بالإنجاز" بتقييم منخفض. The aim of this study is to recognize the prevalence of Job Burnout according to employees working in The Central Directorate of Algiers Post in Boumerdes Province, The study population consisted of all employees working in The Central Directorate of Algeria Post in Boumerdes Province, which are (60) working employees as the study was applied to all of them. To achieve the objectives of the study, the researcher used a scientific questionnaire that is based on two major areas; the first is about the personal information of the respondent. while The second is about the Maslach burnout scale,The collected information was processed in order to prove the hypotheses of the study by using international statistical program (SPSS). The results of the study revealed that there is an average level of job burnout among the employees of The Central Directorate of Algiers Post in Boumerdes Province, The results also demonstrated the existence of a difference in the evaluation of the job burnout dimensions, Where " exhaustion " came in first place with an average evaluation, followed by " depersonalization " in second place with an average evaluation as well, and " lack of personal accomplishment " came in third and last place with a low evaluatio
An analytical study of the reality of the Job Burnout among employees in The Central Directorate of Algiers Post (Boumerdes Province). - According toMaslach Burnout Inventory - Human Services Survey ( MBI – HSS
مقال
Keywords: الإحتراق الوظيفي ; مقياس ماسلاش للإحتراق الوظيفي المخصص للخدمات الإنسانية ; المديرية المركزية لبريد الجزائر ; ولاية بومرداس